Effectiveness of Law on the Implementation of District Government Policy Enrekang About Zakat Management Through the Payroll System Method - Soalehuddin; Agus Muchsin; Rahmawati; Hannani; Mukhtar Yunus (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
The institution of zakat is one of the sources and resources that can be used to reduce poverty. Zakat, which is not at all an act of charity or a voluntary act with good intentions on the part of the giver, is an obligation on the person who pays it. It is the right of the people who need it. By giving zakat, a Muslim and Muslim woman means cleaning up their income and wealth. When the poor take it, they know that they bear no obligation to the giver. The aims and objectives of this research are to provide benefits both theoretically and practically theoretically, namely to enrich and develop the study of legal science in general and especially in Islamic science. Providing references for further researchers and additional library materials for anyone who needs them. Meanwhile, in practical terms, this is to be able to increase knowledge as well as one of the requirements for passing Master's studies and getting an MH degree. And it is hoped that they will be able to understand the legal position of online zakat from a fiqhi perspective. The results of this research show that Zakat is an obligatory worship for Muslims who have assets that meet the mandatory zakat requirements. If the management of zakat payments is carried out optimally, it can become a social instrument to overcome the problem of poverty and unequal income distribution in Indonesia. This means that zakat has a very fundamental meaning. Apart from being closely related to the divine aspect.